Internet violence against chilean feminists and other activists - Cecilia Ananías Soto; Karen Vergara Sánchez (Revista Estudos Feministas, 2019)
This work analyses gender-based violence on Internet which affects both feminists and human rights activists in Chile, giving thus a first approach to a kind of violence that has been overshadowed in Latin America and that has proved recently how dangerous it can be for those who have gone through it. To this end, 163 cisgender heterosexual and transgender women were surveyed through an online questionnaire inside a non-probabilistic sampling method through convenience, as the first research of this topic nationwide. Among the activists interviewed, 73.6% explicitly stated to have been victims of this kind of violence. They suffered mainly verbal abuse (91.7%), harassment (25.8%), threats (22%) and false information published about them (15%). Also, 13.3% stated to have had pictures stolen from their social networks, and another 13.3% received sexually aggressive images and/or videos, which also made evident the non-existent preparation of both the police and the judiciary power while facing those issues, even when they are being denounced. Besides, through an approximation to the aggressors’ speech, it was established that most of them were mainly young and adult men with higher education, who use Internet to spread psychological terror and to make the victims feel they are being constantly observed. This is an urgent problematic that the society needs to address, to avoid an increase between the legal impunity and the reluctance of authorities and citizens to consider it as digital gender-based violence.